Perilaku Dalam Organisasi (Dinamika Organisasi) - Khalifah Maratul Sholihah; Kasful Anwar; Jamrizal Jamrizal (Jurnal Manajemen Riset Inovasi, 2024)
This paper discusses Behavior in Organizations (Organizational Dynamics), this paper aims to find out in depth about Behavior in Organizations (Organizational Dynamics). In organizational behavior you will study three basic things, namely the science of individual behavior, group behavior and organizational behavior itself. This chapter is the beginning of understanding organizational behavior by first understanding individual behavior in the organization. In an organization there are various individuals who have a set of different backgrounds and characteristics that differ from one individual to another such as race, culture, ethnicity, motives, hopes, education, abilities, skills, etc. So a manager must be able to study various individual characteristics from each other to maximize each individual's potential so that they can provide good performance for the organization. Individual behavior tries to analyze the determinants that determine an individual's behavior in an organization, including personality, attitudes, values, and perceptions as well as abilities and skills. By knowing the characteristics of each individual, it is hoped that they can make a maximum contribution to the organization.